Senior Editors’ Notes - Daniel Greenberg, Chikara Onda, Adriana Akers, Winston Christie-Blick, Madeline Dangerfield-Cha (Consilience, 2009)
Dear Readers, I welcome you to meet the leading editorial board of Consilience: The Journal of Sustainable Development. Each senior editor is an inspiring leader and world citizen. I invite you to peruse, below, in addition to the Editor-in-Chief’s note, the notes of each Senior Editor on the written work they advised. -Hannah Lee Editor-in-Chief Scholarly Articles Towards Sustainable Wastewater Reuse in the MENA Region Dr. Maher Abu-Madi, Assistant Professor, Birzeit University Dr. Rashed Al-Sa’ed, Associate Professor, Birzeit University > Note by Chikara Onda When discussing resource management with regards to the Middle East and North Africa (MENA) region, oil is generally the first commodity that comes to mind. Yet, with human populations growing alongside a dwindling base of freshwater resources, the global water crisis is of great salience, especially to areas of low precipitation. In order to bridge the gap in water availability and demand, Abu-Madi and Al-Sa’ed advocate for the reuse of wastewater, which also has the added benefit of mitigating environmental degradation. In this piece, the authors develop a parsimonious Water Reuse Index (WRI). The calculation of this index, they argue, will allow the policy makers to identify the “juncture” in wastewater treatment at which its use as a resource is being limited, be it collection, treatment, or reuse. This piece is therefore not only highly relevant in its subject matter, but also in the way in which it brings policy and academia together. GAD and Gender Mainstreaming: A Pathway to Sustainable Development? Alleta Brenner, London School of Economics > Note by Winston Christie-Blick Over three decades have passed since the 1975 World Conference of the International Women’s Year in Mexico City drew widespread attention to issues of economic, social and political gender inequity in the developing world. Since then, the goals and approaches of those seeking to ensure that members of each sex enjoy equal benefits from development have been varied and constantly evolving. Aims of such development practitioners have spanned from a focus on women’s productive roles and their integration into the economy as valuable agents of economic growth, to increased concern over gender-driven social relations, the social construction of gender identity and the redistribution of power between sexes. This final objective of inter-sex power transfer is a fundamental and provocative element of the Gender and Development (GAD) paradigm presented here in Alletta Brenner’s piece, which discusses the viability of top-down approaches towards greater gender equality in Afghanistan following the U.S. invasion in 2001. Specifically, the initiative of “Gender Mainstreaming” is analyzed as a manifestation of the GAD paradigm—described as an effort to raise awareness of gender inequality while increasing women’s participation in the public sphere. In spite of the convincing case made for a top-down gender-based development effort, Brenner acknowledges and discusses setbacks to the success of Gender Mainstreaming due to both practical problems of implementation in Afghanistan and those more fundamental to the Mainstreaming initiative in general. From Brenner’s account at least two points are clear: if GAD denies men a role in its agenda it will be seen as an overtly threatening force that redistributes power at the expense of males and arbitrarily hurls women into a sphere in which they have not traditionally played (and may not be prepared to play) a role; secondly, it must be recognized that Gender Mainstreaming, and any top-down GAD initiative, is bound to fail if viewed as a pet project of paternalistic outsiders, not rooted in the country of interest’s culture and traditions. At a time when the U.S. and its allies continue to struggle with reconstruction and concomitant development efforts in the Middle East, Brenner’s warning that the numerous shortcomings of Gender Mainstreaming may lead to regress in the effort for gender equality is of extreme relevance. Insofar as Gender Mainstreaming in Afghanistan could be seen as just one experiment in gender-based development that could be instantiated elsewhere in the future, learning from these deficiencies bears significant implications for the livelihoods of millions of women across the developing world, which would be greatly augmented by increased agency in both the public and private spheres. Evaluation of the NZAID Project Scarlett Lopez Freeman, Columbia University Seung Bok Lee, Columbia University Veena Vasudevan, Columbia University Diana Wu, Columbia University The Political Economy of the Resource Curse in Gabon: Lessons for Ghana Richard King, London School of Economics > Note by Daniel Greenberg The “resource curse” theory has lost none of its potency or popularity since it was first formulated. It has been applied to explain situations ranging from violent civil conflict in Africa to resistance to democracy in the Middle East and Latin America. Richard King provides a provocative and thoroughly researched argument, stressing the need for reliable institutions to manage Ghana’s oil. Norway provides perhaps the best case showing that people can design mechanisms and take control of their natural surroundings to avert the pitfalls of the resource curse. Encouragingly, people, and not nature, are the deciders of fate. The Ghanaian government would do well to tighten their political institutions in order to direct their newfound wealth to development rather than to political patronage and possibly war. The stakes could not be higher. Situating Local Knowledge Within Development Agenda: Some Reflections Dr. Toyin Kolawole, University of Sussex > Note by Daniel Greenberg The scene is paradoxical: well-educated, well-dressed European and American technocrats discussing how to “solve” the problems of Africa, Asia, Latin America, in the absence of any Africans, Asians or Latin Americans. The concept of “development” has certainly come under public debate in the recent past. Toyin Kolawole provides a provocative argument for the incorporation of “local knowledge” into the development agenda. What he proposes, essentially, is development from the ground up, assisting the needs of local populations rather than imposing “modernization.” While modern science has yielded tremendous advantages, it can often be reductive, and has not been a panacea in many parts of the developing world. With growing calls for “bottom-up” rather than “top-down” development, Kolawole provides a systematic argument not only for the importance of local knowledge, but for its formalization and reproduction in schools and universities. Agree or disagree, this issue is has the potential to transform the practice of development. Social Responses to Environmental Degradation in Northwest Rural China Scott Moore, Princeton University A. Leung, University of Chicago E. O’Donnell, Michigan State University H. Travis, Central Washington University > Note by Chikara Onda China’s policies constantly seem to be the object of international criticism, be it with regards to its environmental policy or its human rights record. Yet, these “problems” are generally considered as separate entities; seldom is the relation between them considered. In “Social Responses to Environmental Degradation in Northwest Rural China”, Moore et al. consider the incentive structures underlying environmental consciousness in the Shanxi province of China, which is affected by desertification and groundwater depletion. This paper is a prime example of interdisciplinary research in that it brings together two issues that are often brought up with regards to China, environmental degradation and gender equality, making connections between the two, of which many may not have even thought. More specifically, it asks whether the lack of female participation in daily activities affects their ability to act upon their higher environmental awareness, if any. In answering this question, the paper ends up spanning the fields of, environment, anthropology, gender studies, agriculture, policy, and linguistics, among others. How to Get Beyond the Zero-Sum Game Mentality between State and Non-State Actors in International Environmental Governance Dr. Franz Perrez, International Affairs Division, Federal Office for the Environment, Switzerland > Note by Winston Christie-Blick The potentially far-reaching, if not global, effects of nations’ environmental policymaking offer immediate justification for developing and maintaining effective systems of environmental governance that extend across national borders. But on the international scale, environmental policymaking can suffer in quality and legitimacy due to constraints placed on state representatives, who are necessarily disconnected from the multitude of local environmental issues on which their policies are based. Moreover, the inherent pressure on state actors to protect national rather than international interests and their hesitance to sacrifice national development prospects by implementing costly environmental policies—which threaten to diminish short run economic growth in exchange for long run economic and environmental sustainability—further hinders effective international governance. Such obstacles may lead to a failure of national governments to appropriately prioritize pressing environmental concerns over other matters of national importance. Acknowledging this lack of political will to address critical environmental issues on the international scale, Dr. Franz Perrez offers a unique and illuminating glimpse into the inner workings of international environmental governance, stressing the valuable role that non-state actors like non government organizations can play in international governance despite the limitations often put on their involvement. His insights into the state of today’s institutions of environmental governance culminate in an insider’s look at the unproductive, semi-competitive mentality of state and non-state representatives in certain governance processes. As Dr. Perrez asserts, institutions of international governance have much to gain from liberalizing the restrictive, overly formalized format of non-state actor participation and fostering authentic interaction between state and non-state actors. Given the capacity of non-state actors to supply expert knowledge on localized issues, assist in implementation of policies, increase the quality of environmental governance by influencing agenda-setting, and galvanize political will as public advocates for environmental reforms, Dr. Perrez is surely justified in claiming that NGOs ought not be overlooked as key allies in addressing critical and time-sensitive issues of global environmental degradation. Field Notes Communicable Disease Surveillance and Response in Uganda Matthew Cummings, Siena College > Note by Adriana Akers Matthew Cummings’s field note, “Communicable Disease Surveillance and Response in Uganda,” recounts the author’s work with the Epidemiology and Surveillance Division of the Uganda Ministry of Health in the summer of 2008. The note focuses on his travels in the eastern district of Pallisa, where a cholera outbreak had occurred previous to his arrival in the country. Cummings’s team found that various conditions had contributed to the outbreak and made several recommendations to control the disease. Pit latrines needed to be constructed farther from water sources; communities required more supplies like soap and water purification tablets; local doctors needed further cholera-specific training. The field note also touches on unexpected resistance to already available prevention measures: Cummings’s team found that the bitter taste produced by water-purifying tablets caused many to neglect to use them. Cummings focuses on the role of Village Health Teams (VHTs), local residents who are trained to recognize signals of a disease outbreak as well as treat initial symptoms. His field note brings to life our academic knowledge about VHTs and reminds us that supplies and access to medication are not the only important factors in communicable disease prevention and control; local knowledge and local participation are also vital. From the Global to the Local: How International Child Rights in Bangladesh Reach the Grass Roots’ Level Andrea Schapper, University of Bremen > Note by Adriana Akers In her piece, “From the Global to the Local: How International Children’s Rights in Bangladesh Reach the Grassroots Level,” Andrea Schapper investigates how international and national legislation regarding child labor can be transported to local communities. The field note connects global and national legislation with two projects being conducted on the ground in Bangladesh. While Schapper determines that both projects are largely successful in transplanting global and national legislation to the grassroots level, she also recounts the programs’ flaws, providing us with a realistic, fleshed-out account the initiatives. The first case study is the Food for Education Program, which provides qualifying families with a free monthly food ration if their primary-school-aged child attends school on a regular basis. Schapper met with officials involved in the program as well as program participants who attend the Gorad Government Primary School in Savar Upazila. The second program, Prevention and Elimination of Selected Worst Forms of Child Labour in the Informal Economy in Dhaka City, works to reduce the number of children who work in hazardous environments in Bangladesh (the number is currently estimated to be 1.3 million). The program re-introduces younger children to the formal education system and provides a skills-based, vocational training program for older children. The initiative also provides mothers of participants with a micro credit and training to start a business. Schapper met with a technical advisor for the program and mothers who received micro credits through the program. The women that she met with are now all small business owners. Opinion Pieces Illusions of Grandeur: The Role of the Psychosocial in a Sennian Approach to Escaping Urban Poverty Rochelle Burgess, London School of Economics > Note by Adriana Akers In “Supporting Capabilities: Using Psychosocial Concepts to Guide a Sennian Approach to Escaping Urban Poverty,” Rochelle Burgess takes a psychological approach to understanding poverty in Brazil’s favelas, or informal urban slums. The piece is notable because it considers a psychosocial approach—an angle not often used in the field of Sustainable Development—and because it examines the phenomena of informal urban slum communities. The appearance of such communities around city peripheries has rapidly increased in recent years, most notably in the developing regions of Africa, Asia, and Latin America. Burgess’s opinion piece considers concepts developed in renowned economist Amartya Sen’s work Development as Freedom and argues that psychosocial theory can combine with Sennian ideas to build and inform development programs. In particular, Burgess writes that psychosocial theory can help us understand how favela residents can achieve the (political) freedoms that Sen suggests can help individuals escape poverty. Burgess argues that psychosocial barriers like negative social identity, negative social representations, and stigmatization toward favela residents can hinder these individuals from achieving Sennian freedoms on a day-to-day basis. By considering the fields of psychology, economics, and urban studies, the piece takes an interdisciplinary approach toward understanding the case study of Brazilian favelas. Photo Essays India’s Clean Water Access Constraints Daniel Bachhuber, University of Oregon Sustainable Living by the Nomads: Is There Development? Dulguun Batkhsihig, University of London’s School of Oriental and African Studies Images and Voices of Change: Engaging Local Community in Assessing Impact of Millennium Villages Project in their Lives in Sauri Village, Western Kenya Dr. Mary Nyasimi, Columbia University Dr. Joseph Okang’a, CEFORED Institute, Nairobi, KenyaChallenges to the Conservation of River Turtles (spp. Podocnemis) in the Peruvian Amazon Francisco Laso, Columbia University > Note by Madeline Dangerfield-Cha I’m very proud to present this collection of photo essays. The depth and insight that these four authors convey through their artistic vision and compassion is truly humbling. Dr. Mary Nyasimi and Joseph Okang deepened their work at the Millennium Village in Western Kenya by turning the camera over to the villagers and asking for their stories first hand. What results is touching, surprising, and familiar. Franscisco Laso took his camera into the Peruvian Amazon in an attempt to bring largely ignored species decline to light. Daniel Bachhuber brings together loosely-related stories of the Ganges River in India through lively images of life on its banks. Dulguun Batkhishig catalogues the impact of tourism on a small nomadic community by showing intimate, intricate images of their lives as they’ve been lived for hundreds of years, and the threats facing them now. This collection touches three continents. It covers city, forest, field, and river. It assesses the impact of industrial societies on natural resources, of foreign cultures on native ones, on lifestyles in danger, and on lives flourishing. It speaks to sustainable development across the world, and I am honored to present it to you today.